2017
DOI: 10.1021/acs.energyfuels.7b00464
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation into the Production Behavior of Methane Hydrate under Methanol Injection in Quartz Sand

Abstract: In this work, the dissociation behavior of methane hydrate in quartz sand sediment by injecting a thermodynamic inhibitor, methanol (MeOH), was investigated using a one-dimensional experimental apparatus. The experimental results indicated that the hydrate dissociation process included four stages: free gas production, methanol dilution, major hydrate dissociation, and residual gas production. The overall liquid production rate was smaller than the injection rate during the whole production process. The cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 41 publications
0
38
0
1
Order By: Relevance
“…From micro-to macro-scale, various laboratory experimental devices [3,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] combined with state-of-the-art monitoring equipment [18,[26][27][28][29][30][31][32], have been developed to investigate gas hydrate formation processes based on different hypotheses and to determine the optimum parameters for hydrate production. Evidently, it is impractical and challenging to extract intact and undisturbed NGH samples from hydrate-bearing layers.…”
Section: Introductionmentioning
confidence: 99%
“…From micro-to macro-scale, various laboratory experimental devices [3,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] combined with state-of-the-art monitoring equipment [18,[26][27][28][29][30][31][32], have been developed to investigate gas hydrate formation processes based on different hypotheses and to determine the optimum parameters for hydrate production. Evidently, it is impractical and challenging to extract intact and undisturbed NGH samples from hydrate-bearing layers.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, natural gas as a fuel is much more environmentally friendly than coal and oil since it has a high calorific value; when it is burned, only carbon dioxide and water are formed [9,15]. Four main methods of gas hydrate field development have been proposed [16]: depression [17,18], heating [19,20], injection of inhibitors [21][22][23], and replacement with carbon dioxide [24,25]. In this regard, the study of the formation and decomposition of gas hydrates in porous media is a key point for a fundamental understanding of natural gas hydrates' behavior, the development of technologies for their extraction and practical application in the processes of transportation and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [45] showed that the thermal stimulation method (hot water injection) yields gaseous methane at a During depressurization [41,42,[118][119][120], when the operating pressure falls below the equilibrium pressure, the ambient heat is absorbed to dissociate hydrates into gas and water [97]. The production of gas during the depressurization of methane hydrate reservoirs can be divided into three stages (free gas, mixed gas, and gas from dissociated methane hydrate) [125]. During depressurization, no artificial heat is supplied.…”
Section: Exploration Extraction and Transportationmentioning
confidence: 99%